Juridical analysis of the position of laboratory results in proving narcotics crimes in the military environment (Juridical Review in Decision Number 12-K/PMT-II/AU/V/2021) - Sarumpaet, Syawaluddin (Goodwood Publishing, 2024)
Purpose: This study aims to analyze the Juridical Position of Laboratory Results in Proving Narcotics Crimes in the Military Environment (Juridical Review in Decision Number 12-K/PMT-II/AU/V/2021). Research/methodology: This research is a type of normative juridical research using a descriptive analytical approach. The analysis relies on the examination of legal sources and court documents related to the case. Results: Laboratory results serve as very strong and absolute evidence because they are based on measurement and weighing, which contain certainty compared to witness statements. It is impossible to identify narcotic content in blood or urine by visual observation; thus, laboratory tests are indispensable. According to the minutes of the Criminal Laboratory Examination No. LAB 5743/NNF/2020, various items were tested and confirmed to contain methamphetamine. In this context, a negative urine test alone is insufficient to acquit a defendant. Judges must consider all the evidence presented, and a decision must be based on a minimum of two valid pieces of evidence. Conclusion: Even if the urine test result is negative, a guilty verdict can still be rendered if there is other valid evidence supporting the charges. Limitation: This study is limited to a normative juridical review and does not include empirical data from field studies or interviews with legal practitioners. Contribution: This study contributes to the understanding of the evidentiary value of laboratory results in military narcotics trials and provides a juridical framework for evaluating evidence beyond urine test outcomes.